2022
DOI: 10.5603/dk.a2022.0032
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Glycemic Control Status and Serum Level of Vitamin D3 in Patients with Type 2 Diabetes: A Cross-Sectional Study

Abstract: Objective: This study aimed to assess the association between glycemic control status and serum levels of vitamin D3 in Iranian patients with type 2 diabetes (T2D). Materials and methods: This was a cross-sectional study on 452 patients with T2D in Tehran, Iran, performed between September 2019 and September 2020. We assessed the diabetes laboratory test and vitamin D3 level in all participants using the Enzymatic Glucose Oxidase method. Data were analyzed using SPSS version 24. Results: a total of 452 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…in this issue, ehsan aliniagerdroudbari et al from tehran, iran reported a higher prevalence of vitamin d deficiency in people with type 2 diabetes (vitamin D deficiency was reported in 48%, insufficiency in 21.5%, and sufficiency in 30.5%) and significant direct association between vitamin D and HbA1c levels [11]. The geographical location and air pollution in tehran may likely be associated with a high prevalence of vitamin D deficiency in this population.…”
Section: Vitamin D and Diabetes: Association Vs Causation?mentioning
confidence: 80%
“…in this issue, ehsan aliniagerdroudbari et al from tehran, iran reported a higher prevalence of vitamin d deficiency in people with type 2 diabetes (vitamin D deficiency was reported in 48%, insufficiency in 21.5%, and sufficiency in 30.5%) and significant direct association between vitamin D and HbA1c levels [11]. The geographical location and air pollution in tehran may likely be associated with a high prevalence of vitamin D deficiency in this population.…”
Section: Vitamin D and Diabetes: Association Vs Causation?mentioning
confidence: 80%